Effects of feeding sago pith residue on growth performance of rabbits - Malahubban, Masnindah; M. S., Firdaus; H., Mohammad Nasir; M., Jiwan (2009)
An experiment was conducted to determine the effects of feeding sago pith residue on growth performance of 2-month-old New Zealand White rabbits. Eighteen rabbits were allocated to individual cages for three treatments in which they were fed diet with commercial rabbit pellet (Control); 40% sago pith residue (40% SPR) and 70% sago pith residue (70% SPR). The rabbits have access to water and feed ad libitum for 60 days. The result of average daily gain (ADG) of the 2 month-old rabbits fed with different levels of SPR was found to be significantly lower in the diet supplemented with 70% SPR (2.38 ± 0.006 g/d). The ADG of rabbits fed with Control (13.03 ± 0.012 g/d) and 40% SPR (10.98 ± 0.010) were significantly higher compared to the 70% SPR. Results of average daily intake (ADI) showed that rabbits fed on Control and 40% SPR were almost similar and significantly different (P>0.05) at 67.80 ± 1.736 g/d and 65.72 ± 1.436 g/d, respectively. However, ADI of rabbits fed with 70% SPR was significantly lower at 49.69 ± 0.709 g/d. The feed conversion ratio (FCR) of rabbits fed 70% SPR was found to be significantly different (P<0.05) than those rabbits fed Control and 40% SPR diets. This study suggest that rabbits can utilize SPR for growth but inclusion of SPR should not exceed 40% to obtain good growth response and feed conversion efficiency.